Pedagogical practices for developing the scientific critical spirit in the student - Chimendes, Vanessa Cristhina Gatto [UNESP]; Andrade, Herlandí de Souza [UNESP]; Rosa, Adriano Carlos Moraes; Miranda, Yara Cristina Costa Rocha; Silva, Messias Borges [UNESP] (My University, 2018)
The study and knowledge of various disciplines makes it possible to overcome the limits imposed by science itself. In this sense, the construction of knowledge today requires a new posture of the researcher, requires a broader and holistic view, with the interaction of the various areas, both in the expansion and in the deepening of the treatment of complex studies. Thus, the objective of this work is to identify the pedagogical practices for the development of the critical scientific spirit in the student and to stimulate the entrepreneurial spirit in the learning environment. For the accomplishment of this research, a structured questionnaire was elaborated and sent to the researchers that belong to the database of the CNPq. After discussing the results found, it was possible to understand that for the formation of the citizen it is important and necessary to develop the critical scientific spirit, which is another look, is to look at the world in various ways. In this context, the new order makes the university feel the importance of adopting new curricular designs, innovations of a technological nature and instrumental knowledge. In this way, it was possible to conclude that the growing relationship between science, technology and entrepreneurship gives opportunities to multi, inter and transdisciplinary actions, reflecting on its mission, articulation with other segments and under the foundation of fair and socially inclusive manifestations.

O estudo e o conhecimento de várias disciplinas possibilitam a superação dos limites impostos pela própria ciência. Neste sentido, a construção do conhecimento, hoje, exige uma nova postura do pesquisador, exige uma visão mais ampla e holística, com a interação das diversas áreas, tanto na ampliação, quanto no aprofundamento no trato de estudos complexos. Assim, o objetivo deste trabalho é identificar as práticas pedagógicas para o desenvolvimento do espírito crítico científico no aluno e para estimular o espírito empreendedor no ambiente de aprendizagem. Para a realização desta pesquisa, foi elaborado um questionário estruturado e enviado aos pesquisadores que pertencem à base de dados do CNPq. Após discutir sobre os resultados encontrados, pôde-se entender que para a formação do cidadão é importante e necessário o desenvolvimento do espírito crítico científico, que é outro olhar, é olhar o mundo de várias maneiras. Nesse contexto, a nova ordem faz com que a universidade sinta a importância de adotar novos desenhos curriculares, inovações de natureza tecnológica e conhecimentos instrumentais. Desta forma, foi possível concluir que a relação crescente entre ciência, tecnologia e empreendedorismo dá oportunidade às ações multi, inter e transdisciplinares, refletindo sobre sua missão, a articulação com os demais segmentos e sob o alicerce de manifestações justas e socialmente inclusivas.
Práticas pedagógicas para desenvolver o espírito crítico científico no aluno
Keywords: Innovation in teaching-learning; Inovação no ensino-aprendizagem; Interdisciplinaridade; Interdisciplinary; Multidisciplinaridade; Multidisciplinary; Pedagogical practices; Práticas pedagógicas; Transdisciplinaridade; Transdisciplinary